THE ROLE OF URBAN SPATIAL CONFIGURATION IN SHAPING PERCEPTIONS OF INSECURITY IN PUBLIC SPACES (CASE STUDY: PUBLIC SPACES IN THE CITY OF SURABAYA) - Dimas Widya Putra, R
Research on feelings of insecurity in public spaces is often conducted by examining the influence of design/components, management, and internal supervision within public spaces. The results of research on feelings of insecurity in public spaces show varying outcomes and suggest the presence of suspected factors outside of public spaces (space configuration) contributing to the formation of insecurity. To what extent external factors affect feelings of insecurity is still indicative in explaining inconsistent results related to internal factors within public spaces that affect insecurity. This research aims to explore and explain the influence of spatial configuration in shaping feelings of insecurity in public spaces. This research is exploratory in nature with a deductive approach and quantitative methods. Correlation statistical analysis is used to examine the relationship between dimensions of insecurity and land use configuration variables; Structural Equation Modeling (SEM) analysis is used to confirm the influence of individual internal variables on the relationship between land use configuration and insecurity, and spatial analysis is used to observe the influence of composite land use configuration variables on dimensions of insecurity. The research results indicate that from the correlation analysis, there is no relationship between spatial configuration variables and insecurity. From the SEM analysis, it is shown that the mediation of gender, occupation, income, age, number of family members, and self-difference cannot mediate, so spatial configuration variables do not directly influence insecurity. From spatial analysis, it is shown that the characteristics of spatial configuration found mostly differ from the emerging hypotheses. The findings of this study contradict the opinions of Ceccato (2020) and Kamalipour et al. (2014), who stated that there is an indication that external variables outside of public spaces influence insecurity. This research also found that socio-demographic variables (mediation) cannot mediate the relationship between land use configuration variables and insecurity. This argument refutes the theories of Soomeren (1996), Gans (1982), and Hunter (1975) that socio-demographic variables affect insecurity in public spaces. This research also indicates that the theory of Jacobs (1961) that internal variables are still relevant in reducing insecurity in public spaces. There is an indication of city policies in Surabaya as an external factor outside of public spaces.